DIFFERENTIATION OF FORAMINIFERAL ASSEMBLAGES AND DYNAMICS OF THEIR TAXONOMIC DIVERSIFICATION IN THE JURASSIC - Kuznetsova K.I. (My University, 1998)
Data on Jurassic foraminifers from key localities in continents and oceans is analyzed. Their distribution range spans the stratigraphic interval from the Aalenian to the Tithonian equal to 32 million years. Among 23 localities (including 7 Jurassic sections recovered by deep sea drilling), data for 9 are originally obtained. Information on other localities is presented on the basis of published data. The assemblages studied comprise three types of foraminiferal fauna corresponding to those distinguished by V.A. Basov for different climatic zones: Arctic (cold), Boreal (moderately cold), and Tethyan (warm tropical to subtropical). It is established that faunas different not only in dominant components but also in taxonomic composition of a high rank were characteristic of the Tethyan and Peritethyan regions in the Jurassic. Assemblages of different types are present in adjacent sections and even in the same section. Neither climatic fluctuations nor penetration of cold or warm water masses, as well as fauna migration and invasion, can explain this phenomenon. The mosaic distribution of faunal assemblages and alternation of different fauna types are the result of bathymetric differentiation and related environmental factors such as temperature, type of bottom substrate, hydrodynamics, and distance to the shore line.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская